Project on Human Development in Chicago Neighborhoods (PHDCN): Child and Adolescent Behavior Rating Scale, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Child and Adolescent Behavior Rating Scale. It obtained an interviewer rating of the behavior of all subjects in Cohorts 0, 3, 6, 9, and 12. It recorded the amount of time the interviewer spent observing the subject and whether this observation took place only during the interview with the subject or during the interview and at other times. The subject was also rated on various behaviors. This data collection is closely related to PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): CHILD AND ADOLESCENT BEHAVIOR RATING SCALE, WAVE 2, 1997-2000 (ICPSR 13610).